Diversity fluctuations of the microbial community during annual Microcystis blooms within Lake Okeechobee, FL - Samuel, Paisley S.; Lopez, Jose V. (Frontiers in Water, 2025)
Lake Okeechobee, an essential Floridian freshwater ecosystem, has experienced water quality decline due to nutrient pollution since the 19th century. In recent decades, harmful cyanobacterial blooms (cyanoHABs), primarily caused by Microcystis aeruginosa, have increased in frequency and intensity, threatening the lake’s ecosystem. This study investigates the impacts of annual cyanoHABs on the microbial communities in Lake Okeechobee over 3 years by highlighting patterns in the taxonomic dynamics and microbial diversity. From March 2019 to October 2021, 541 surface water samples and corresponding environmental variables were collected and analyzed from 21 routinely monitored sites within Lake Okeechobee using 16S V4 amplicon sequencing techniques. Dominant taxa remained consistent throughout the sampling period, with noticeable fluctuations occurring primarily in 2019 at the order and family levels. Significant spatial differences in microbial composition across all 3 years suggest stable biogeographical patterns across ecological zones within the lake. Microcystis relative abundance and microcystin had the strongest environmental influence on microbial diversity. Microcystis relative abundance was also found to negatively impact the microbial diversity of the lake while strongly correlating with several environmental factors, including temperature, total depth, and nitrate + nitrite concentrations. A co-occurrence network suggested that over 20 microbial genera may influence commensal, mutualistic, or antagonistic relationships with Microcystis. For example, predatory Bradymondales sp. and Bdellovibrio sp. as well as microcystin-degrading Cupriavidus sp. were detected. These findings highlight the importance of identifying and monitoring specific bacterial populations to aid in the monitoring of Microcystis cyanoHAB formation and ecosystem effects.